Food Ordering System in the School Canteen for Teachers - Abdul Rahman, Dina Safiah; Othman, Muhaini (Applied Information Technology And Computer Science, 2024)
The Food Ordering System in the School Canteen for Teachers is a web-based digital platform designed to streamline food ordering, addressing the inefficiencies of manual processes and limited menu options, enhancing teacher satisfaction and productivity. Through a user-friendly online platform, it offers easy access to menus, streamlined orders, and flexible payments option, aiming to revolutionize the manual and walk-in food ordering process within canteen operations at Sekolah Menengah Kebangsaan Tengku Ampuan Jemaah. Developed  using the Software Prototyping Model, this system was built with Visual Studio Code and a database managed by Laragon. It promises to modernize the ordering experience, offering a more efficient and satisfying ordering experience, ultimately benefiting both teachers and canteen management.